Malesia Bryophytes Diversity - Ferdinand Susilo; Muhammad Komarul Huda; Hanifah Mutia Z.N. Amrul (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Bryophyte is a division of plants that lives on land, generally it is green and reproduces through spores, has ecological and economic functions, and plays an important role in forest ecosystems. It spreads out almost in all parts of the earth with different characters in each group. It is divided into 3 groups, namely liverwort, true moss, and hornwort, which are phylogeny and true liverwort is in the same lineage. The number of bryophytes species is around 18000 with the largest distribution area of bryophyte diversity in tropical and subtropical latitudes, such as the Malesia region which includes Malaysia, Indonesia, Timor Leste, Papua New Guinea, the Philippines, and Brunei. Various studies were carried out related to the diversity of bryophyte, especially in the Malesia region, and found various types including new species, new records, and new characters.